Fragilidade de idosos em contexto de alta vulnerabilidade social : identificação de fatores associados - Menezes, Ana Laura Costa (2017)
Introduction: Frailty, defined as a multifactorial syndrome that can cause functional disability and an increased risk of comorbidities. Older people in a context of high social vulnerability may present greater risk of frailty. The identification of frailty’s levels and associated factors in the elderly in situations of social vulnerability is fundamental for a social care and health care therapy. Objective: To identify the factors associated with frailty in the elderly living in the context of high social vulnerability. Methodology: This is a correlational, cross-sectional research. The data collection was carried out at the participants' home with application of the instruments: Socio-demographic Questionnaire; Fried Frailty Phenotype Assessment; Mini Mental State Examination; Geriatric Depression Scale; Katz Index of Independence in Activities of Daily Living; Lawton And Brody Instrumental Activities Of Daily Living; Advanced Daily Life Activity Questionnaire - FIBRA network; International Physical Activity Questionnaire; Timed Up and Go Test; and Social Support Scale of the Medical Outcome Study. The Research Ethics Committee of the Federal University of São Carlos approved the project (Opinion No. 1,207,390). Logistic regression was performed to analyze the data. Results: Of the 304 elderly evaluated, 56,9% were female, 53,5% were aged between 60 and 69 years, 12.2% were classified as non-fragile, 60.5% as pre-fragile and 27.3% classified as fragile. The main factors associated with fragility in the studied sample were presence of depressive symptoms (OR: 1.9 95% CI: 1,1 – 3,7), mobility deficit (OR: 3.0 95% CI: 1,5 – 5,8), occurrence of two or more falls within 12 months (OR: 3,1 95% CI: 1,4 – 7,1) and low level of physical activity (OR: 5.2 95% CI: 2,5 – 11,0). Conclusion: The associated factors confirm the relationship between deficits in the physical and psychological aspects resulting from the aging process and socioeconomic conditions with the presence of frailty, in order to meet the national and international publications on the subject. The present study presented contributions so that new public policies can be created and new actions can be planned and implemented by health institutions and professionals, aiming at the promotion of health, prevention of associated factors, reversion and impediment of the progress of frailty, considering the negative impact it generates on the life of the elderly individual.